2007
DOI: 10.1590/s1516-31802007000300011
|View full text |Cite
|
Sign up to set email alerts
|

Vocal fold immobility after thyroidectomy with intraoperative recurrent laryngeal nerve monitoring

Abstract: CONTEXT AND OBJECTIVE: Intraoperative nerve monitoring has emerged as a valuable tool to facilitate recurrent laryngeal nerve identification during thyroid surgery, thereby avoiding its injury. The aim was to evaluate vocal fold mobility in patients who underwent thyroidectomy with intraoperative nerve monitoring. DESIGN AND SETTING: Cohort formed by a consecutive series of patients, at a tertiary cancer hospital. METHODS: The subjects were patients who underwent thyroidectomy using intraoperative laryngeal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…Another related study by Netto Ide et al (2007) also claimed that the use of IONM did not decrease VC paralysis in comparison with a control group who did not undergo neuromonitoring. This study used IONM as a means to identify the RLN.…”
Section: Discussionmentioning
confidence: 94%
“…Another related study by Netto Ide et al (2007) also claimed that the use of IONM did not decrease VC paralysis in comparison with a control group who did not undergo neuromonitoring. This study used IONM as a means to identify the RLN.…”
Section: Discussionmentioning
confidence: 94%
“…The characteristics of the 43 selected studies are shown in Table I through Table III 8–51. Baseline characteristics are provided in Table IV.…”
Section: Resultsmentioning
confidence: 99%
“…Despite widespread and increasing use of this technology, true vocal cord palsy and paralysis as a result of iatrogenic injury to the RLN persist. The overall incidence of temporary injury is 2-8 %, while that for permanent injury is between 0.5 and 3 % [8][9][10][11][12].…”
Section: Historymentioning
confidence: 99%